Efeito estrogênico sobre a expressão do receptor de membrana para estradiol GPER 1 em tecidos secretores ou alvos para a ocitocina - Mauro Sergio Batista da Silva (2014)
The oxytocin is a hormone produced mainly in hypothalamic nuclei and released in the posterior pituitary gland lobe; its effects described in the literature are versatile. The oxytocinergic signaling occurs via the oxytocin receptor (OTR) in target tissues such as the uterus and anterior pituitary gland. The modulation of oxytocinergic action occurs mainly by estrogens in order to increase the efficiency of target tissue response. The estrogenic activity operates through classical receptors ER and ER, as well as rapid responses using recently described receptors. Those include the G protein-coupled estrogen receptor named GPER1. This study aimed to identify the expression profile of GPER1, by real-time PCR and immunohistochemistry, in both oxytocin secreting and target tissues during the female estrous cycle in rats, as well as the effects of estradiol and progesterone on this expression. Three-month old female rats had the estrous cycle followed during at least fifteen days and euthanasia was performed in each phase of the cycle: diestrus, proestrus morning (9:00h), proestrus afternoon (17:00h), estrus and metaestrus. During the proestrus afternoon, we found higher levels of GPER1 mRNA and protein in the PVN compared with the other phases. Gene or protein expression for the estradiol receptor in the SON did not vary over the cycle. The anterior pituitary showed higher expression of GPER1 mRNA or protein on the afternoon period of proestrus. In addition, the results showed that OTR expression was higher on the proestrus afternoon. Ovariectomized animals were treated for four days as follow: corn oil (vehicle); estradiol (E2); estradiol for four days and progesterone on forth day (E2+P4); or corn oil for four days and on forth day with an injection of progesterone (P4). Ovariectomized treated with vehicle had an increase in the expression of the gene gper1 while administration of E2 or E2+P4 significantly decreased the expression of the receptor in the pituitary and uterus. On the other hand, administration of ovarian steroids increased expression of OTR. Our results show that the expression of GPER1 is higher during the proestrus afternoon, which coincided with a previously described increase of oxytocin and gonadotropin secretion in females. The expression of GPER1 depends of the estradiol variation of estrous cycle in secretory and targets tissues for oxytocin, and estradiol administration reduces its expression in target tissues. The greater activation of GPER1 during proestrus afternoon might be linked to higher oxytocin secretion in females during their fertile period. The present study concludes that GPER1 expression shows variations in producing oxytocin nuclei 9 as well as target tissues for the peptide according to the different stages of the estrous cycle. Those changes in expression of GPER1 following changes of expression of oxytocin and its receptor on target tissues to this hormone. In addition, ovarian steroids modulate the pituitary expression of the estradiol receptor.